Retrospective Evaluation of Nosocomial Bacterial Infections and Their Antimicrobial Resistance Patterns Among Hospitalized Patients in Mogadishu, Somalia - Sheikh Omar NM; Erismis B; Muse Osman M; Garba B; Hassan MA; Akuku IG (Infection and Drug Resistance, 2023)
Nasteho Mohamed Sheikh Omar,1 Betul Erismis,2 Marian Muse Osman,1 Bashiru Garba,3,4 Mohamed Abdulahi Hassan,3 Isaiah G Akuku5 1University of Health Sciences Turkey, Mogadishu Somalia-Turkey Recep Tayyip Erdoğan Training and Research Hospital, Mogadishu, Somalia; 2University of Health Sciences, Bakirkoy Dr Sadi Konuk Education and Research Hospital, Istanbul, Turkey; 3Dr Sumait Hospital, Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, 2526, Somalia; 4Department of Veterinary Public Health and Preventive Medicine, Faculty of Veterinary Medicine, Usmanu Danfodiyo University, Sokoto, Sokoto State, Nigeria; 5Institutes of Tropical and Infectious Diseases, University of Nairobi, Nairobi, KenyaCorrespondence: Mohamed Abdulahi Hassan, Tel + 252 61 5987780, Email modhassan@simad.edu.soBackground: Nosocomial infection constitutes a significant public health challenge globally, with resource-limited countries bearing the greatest burden. Sadly, the emergence of drug-resistant strains of these pathogens have worsened the already precarious situation.Methods: This study aimed to determine the incidence of nosocomial infections, the causative agents, and their antimicrobial susceptibilities among patients admitted to a tertiary hospital in Mogadishu, Somalia. The study included patients who had positive cultures 48 hours after admission. Abstracted data include the patient’s demographic, infection outcome, the agents involved, and the site of infection.Results: A total of 330 patients were found to have acquired nosocomial infection, comprising 100 (30%) patients from the ICU department. The median age for the patients in this study was 36 years. Patients who died of all-cause mortality were older than those discharged. Most of the bacteria were collected from sepsis/bloodstream infections (34%) dominated by Staphylococcus aureus (42.1%), Acinetobacter baumannii (14.0%), Escherichia coli (14.0%), and Klebsiella spp. (7.0%). Urinary tract infections were mainly associated with Escherichia coli (37.5%), Staphylococcus aureus (18.8%), and Klebsiella spp. 50% of all microorganisms were multidrug-resistant.Conclusion: The findings of this study suggested that hospital infection control and prevention strategies need to be strengthened to improve the quality of care among hospitalized patients.Keywords: healthcare-associated infections, multi-drug resistant, infectious diseases, Somalia, nosocomial infection